Vulnerability to climate change of managed stocks in the California Current large marine ecosystem - McClure, Michelle M.; Haltuch, Melissa A.; Willis-Norton, Ellen; Huff, David D.; Hazen, Elliott L.; Crozier, Lisa G.; Jacox, Michael G.; Nelson, Mark W.; Andrews, Kelly S.; Barnett, Lewis A.K.; Berger, Aaron M.; Beyer, Sabrina; et al. (Frontiers in Marine Science, 2023)
Understanding how abundance, productivity and distribution of individual species may respond to climate change is a critical first step towards anticipating alterations in marine ecosystem structure and function, as well as developing strategies to adapt to the full range of potential changes. This study applies the NOAA Fisheries Climate Vulnerability Assessment method to 64 federally-managed species in the California Current Large Marine Ecosystem to assess their vulnerability to climate change, where vulnerability is a function of a species’ exposure to environmental change and its biological sensitivity to a set of environmental conditions, which includes components of its resiliency and adaptive capacity to respond to these new conditions. Overall, two-thirds of the species were judged to have Moderate or greater vulnerability to climate change, and only one species was anticipated to have a positive response. Species classified as Highly or Very Highly vulnerable share one or more characteristics including: 1) having complex life histories that utilize a wide range of freshwater and marine habitats; 2) having habitat specialization, particularly for areas that are likely to experience increased hypoxia; 3) having long lifespans with low population growth rates; and/or 4) being of high commercial value combined with impacts from non-climate stressors such as anthropogenic habitat degradation. Species with low or Moderate vulnerability are either habitat generalists, occupy deep-water habitats or are highly mobile and likely to shift their ranges. As climate-related changes intensify, this work provides key information for both scientists and managers as they address the long-term sustainability of fisheries in the region. This information will inform near-term advice for prioritizing species-level data collection and research on climate impacts , help managers to determine when and where a precautionary approach might be warranted, in harvest or other management decisions, and help identify habitats or life history stages that might be especially important to protect or restore